Financial and Economic Aspects of Monitoring Social and Spatial Development of Rural Territories - TARANOVA, Irina Viktorovna; USENKO, Lyudmila Nikolaevna; USENKO, Anastasia Michailovna; NOVOSYOLOVA, Natalya Nikolaevna; NOVOSYOLOV, Sergey Nicolaevich (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
An important scientific aim in modern agrarian policy is to develop methodological support for the monitoring and assessment of the level of territorial distribution and specialization of the agricultural sector of the region. Thus it is important that regional power institutes develope the corresponding organizational and economic regulators to stimulate development of specialization of certain territories and their effective functioning. This will allow diagnosing and smoothing imbalances existing in concentration of productive forces considering features of the natural, market, organizational and administrative environment of municipal districts. Besides the author’s system of organizational-economic regulators, the authors established a system of indicators to assess the level of social development of rural areas in the article. These indicators were divided into 4 groups, the complex use of which will allow monitoring the level of social development of rural settlements: demographic, infrastructural, social indicators of activity of the agricultural organizations and the indicators to measure the level of living of the population. Such system of indicators allows estimating interrelation between the level of social development of rural territories and specialization of agricultural production of the region.
Keywords: economy, agricultural industry, branch monitoring, specialization, spatial placement of production objects, rural territories, social infrastructure